REFORMS IN THE DEVELOPMENT OF THE COTTON GINNING INDUSTRY - Xolmanova Feruza Uralovna (Journal of Learning on History and Social Sciences, 2024)
The history of the development of the agricultural sector in the Republic of Uzbekistan entered a new stage after the years of independence. Due to the fact that Surkhandarya region mainly specializes in cotton cultivation, the cotton ginning industry has a special place in the oasis. During the years of independence, new cotton ginning factories were built and put into operation in Surkhandarya, and great changes took place in the field of light industry